(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
In every sphere a lot of people come across various difficulties such as during the translating process and everybody wants to improve and correct his or her mistakes. For that issue they need any correction for their interpretation. Thus, it is raised by Mackintosh (1995: 126), is "correction":“Correction in simultaneous is more difficult and many feel can only be attempted if the students’ performance is recorded and then compared to the original. Too much attention to terminology and focusing on the words used by a student is usually counterproductive in that it distracts attention from the substance of the message. Correction is a subject on which the literature has little or nothing to say. It is virtually uncharted territory and the references are mainly anecdotal”.